Employability Skills Development Approaches: An Application of Importance-Performance Analysis and Analytic Network Process - Islam, Rafikul; Abdul Hamid, Mohd Shukri; Abd. Manaf, Noor Hazilah (2012)
In the challenging economic world, employers are looking for employees who are able drive organizations to compete successfully in the market. Graduates should equip themselves with the relevant employability skills as needed by the employers. Therefore, higher education institutions must evaluate the effectiveness of employability skills development approaches on graduates’ employability skills. The main objectives of this study are to determine importance weights of Malaysian graduates’ employability skills and to identify the most effective employability skills development approaches. In general, the result of the analytical network process (ANP) shows that the employers placed “ability to speak fluently in English” has highest important weight, followed by “ability to write effectively in English” and. “ability to think critically”. Meanwhile, the results of limit supermatrix show that the most effective employability skills development approach is “work integrated learning”, with a percentage priority of 19.7. The next more effective approach is ‘stand-alone subject model” with 18.5 percent and then followed by academic support programme, embedded subject model, non-academic support programme and campus life activities.